Geography vs. institutions at the village level - Michael Grimm; Stephan Klasen (Center for Economic Studies and ifo Institute (CESifo), 2008)
There is a well-known debate about the roles of geography versus institutions in explaining the long-term development of countries. These debates have usually been based on cross-country regressions where questions about parameter heterogeneity, unobserved heterogeneity, and endogeneity cannot easily be controlled for. The innovation of Acemoglu, Johnson and Robinson (2001) was to address this last point by using settler mortality as an instrument for geography-induced endogenous institutions and found that this supported their line of reasoning. We believe there is value-added to consider this debate at the micro level within a country as particularly questions of parameter heterogeneity and unobserved heterogeneity are likely to be smaller than between countries. Moreover, at the micro level it is possible to identify more precise transmission mechanisms from geography via institutions to economic development outcomes. In particular, we examine the determinants of economic development across villages on the Indonesian Island of Sulawesi and find that geography-induced endogenous emergence of land rights is the critical institutional link between geographic conditions and technological change. We therefore highlight and empirically validate a new transmission channel from endogenously generated institutions on economic development.
Keywords: K11; O12; Q12; 330; geography; migration; land rights; institutions; technology adoption; agricultural development; Indonesia; Dorfentwicklung; Landwirtschaftliche Entwicklung; Agrargeographie; Agrarverfassung; Technologiewahl; Celebes; Entwicklung; Geographie; Institutionalismus